The Role of Emotional Service Expectation Toward Perceived Quality and Satisfaction: Moderating Effects of Deep Acting and Surface Acting - Jeong, Ji Youn; Park, Jungkun; Hyun, Hyowon (Frontiers in Psychology, 2019)
A conceptual model articulating the nature of customer expectations and satisfaction over services was proposed with emotional factors. Five propositions about consumer emotional service expectations as a primary antecedent toward confirmation, perceived quality, and satisfaction were provided. As moderators, two dimensions of consumer detection of emotional labor (i.e., detecting deep acting and surface acting) were imposed on each of the relationships. Evidence demonstrated the roles of emotional service expectation in service confirmation and satisfaction. The moderating effects of consumer detection of employees’ emotional strategies were limited to the relationship between emotional service expectation and confirmation; its relationship was weakened by detections of surface acting while other relationships were not moderated by detections of deep nor surface acting. Structural equation modeling analyses were conducted using online survey data targeting consumers in the hotel / restaurant industry.